PENGARUH INSENTIF DAN KOMITMEN KERJA TERHADAP RETENSI KARYAWAN PADA ORGANISASI - Jumawan Jumawan; Hadita Hadita; Alfin Adam; Aldino Febriyanto; Muhammad Rizky Gemis; Ri’fan Ahmadi; Rizky Edi Nurdiansyah; Sandy Pangestu (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Efforts made by an organization to retain employees who perform well and have high potential to remain in the organization are known as Employee Retention. This article reviews the influence of Employee Retention, namely: Incentives and Work Commitment. The author of this article aims to develop hypotheses regarding the influence of variables on each other for use in further research. The approach used in this research is the Descriptive Approach. In an effort to increase employee retention, organizations can use attractive incentives to encourage employees to stay with the organization. Apart from that, you can also pay attention to employee work commitment. This can be done through effective communication, clear career development, superior support, and an inclusive organizational culture. The results of this literature review article are: 1) Incentives influence employee retention; 2) Work Commitment influences Employee Retention; 3) Incentives and work commitment both influence employee retention in the organization.